Analisis Dinamika Kelompok pada Gapoktan Sekar Sari Desa Pangean Kecamatan Maduran Kabupaten Lamongan - SURTANTIN, ELISA; SUTJIPTA, NYOMAN; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.3, No.2, April 2014, 2018)
Analysis of Group Dynamics at the Sekar Sari Farmers Group, Pangean Village, Maduran Sub-District of Lamongan Regency Group dynamics is a branch of social science that studies the strengths that exist in the group, looking for the cause, and the effect on individuals and groups to act dynamically. Group dynamics can determine group behavior and group members' behavior to achieve common goals. The study aims to describe group dynamics at the Sekar Sari Farmers Group. The location of the research was determined purposively by the Sekar Sari group of Pangean farmers, Maduran Subdistrict, Lamongan Regency with the population of 131 people and the sample was 58 people based on the slovin formula and the data were analyzed by using descriptive analysis. The group dynamics of the Sekar Sari farmer group were viewed through a psychological approach that classified as high category with a percentage of 73.7%. Group dynamics is seen through a sociological approach with very high category of 78.1%. The influence of sociological approach to group dynamics on the Sekar Sari farmers group is higher than the psychological approach. The combined members of the Sekar Sari farmer group are expected to further enhance group cohesiveness, the organizers are expected to pay more attention to the farmer groups, and all members of the farmers group are expected to behave dynamically to achieve common goals.